Analisis Perencanaan Sumber Daya Manusia Keperawatan dan Kebidanan di Rumah Sakit Umum Daerah Siti Fatimah Provinsi Sumatera Selatan - Zoon, Thonel; Lisdiana, Lisdiana; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
Planning Standards for Nursing Staff Needs can be done using various existing approaches, including referring to Permenkes No. 3 of 2020 concerning Hospital Classification and Licensing, also determined based on bed availability and types of hospital, BOR, patient dependency level, effective hours of service. planning for nursing staff needs can also refer to the Decree of the Mi-nister of Health, No. 262/Menkes/Per/VII/1979 concerning the calculation of labor needs based on the comparison between the number of beds available in a certain hospital class with certain types of staff categories. This study aims to analyze Nursing and Midwifery Staff Planning at the Siti Fatimah Regional General Hospital, South Sumatra Province. The problem in the study is that the current number of nursing human resources is not proportional to the number of beds and visits or patient actions and the recruitment process has not been carried out directly by the hospital, but is carried out by the South Sumatra Provincial Health Office. The data analysis tech-nique used in this research is qualitative data analysis technique. This study shows that: overall, Nursing and Midwifery Human Resource Planning at the Siti Fatimah Regional General Hospital, South Sumatra Province has been running as it should. Although in its implementation there are still obstacles in terms of the number of nursing human resources currently available, it is not proportional to the number of beds and visits or patient actions and the recruitment process has not been carried out directly by the hospital.